Scenario-Based Techno-Economic Analysis of Steam Methane Reforming Process for Hydrogen Production - Shinje Lee; Hyun Seung Kim; Junhyung Park; Boo Min Kang; Churl-Hee Cho; Hankwon Lim; Wangyun Won (Applied Sciences, 2021)
Steam methane reforming (SMR) process is regarded as a viable option to satisfy the growing demand for hydrogen, mainly because of its capability for the mass production of hydrogen and the maturity of the technology. In this study, an economically optimal process configuration of SMR is proposed by investigating six scenarios with different design and operating conditions, including CO2 emission permits and CO2 capture and sale. Of the six scenarios, the process configuration involving CO2 capture and sale is the most economical, with an H2 production cost of $1.80/kg-H2. A wide range of economic analyses is performed to identify the tradeoffs and cost drivers of the SMR process in the economically optimal scenario. Depending on the CO2 selling price and the CO2 capture cost, the economic feasibility of the SMR-based H2 production process can be further improved.